1999
DOI: 10.1128/jcm.37.8.2674-2677.1999
|View full text |Cite
|
Sign up to set email alerts
|

Use of Granada Medium To Detect Group B Streptococcal Colonization in Pregnant Women

Abstract: Direct inoculation onto Granada medium (GM) in plates and tubes was compared to inoculation into a selective Todd-Hewitt broth (with 8 μg of gentamicin per ml and 15 μg of nalidixic acid per ml) for detection of group B streptococci (GBS) in pregnant women with 800 vaginal and 450 vaginoanorectal samples. Comparatively, GM was found to be as sensitive as the selective broth for the detection of GBS in vaginal specimens and more sensitive than selective broth for the detection of GBS in vaginoanorectal samples … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 66 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…However, variable results have been reported using different media preparations while studying direct plating versus subculture from Lim broth. Some studies found comparable sensitivity of direct plating on a differential (Granada) medium compared with Lim broth enrichment (Gil et al , 1999; Votava et al , 2001), whereas other reports (De la Rosa et al , 1992; Rosa-Fraile et al , 1999) suggested that direct plating on chromogenic and or selective media was significantly less sensitive (Overman et al , 2002; Nomura et al , 2006). Comparing direct plating on SBS or CNA (bioMérieux) to that of plating on the same media after Lim broth enrichment was found to be equally sensitive with no significant advantage for enrichment (Tazi et al , 2009; El Aila et al , 2010; Louie et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…However, variable results have been reported using different media preparations while studying direct plating versus subculture from Lim broth. Some studies found comparable sensitivity of direct plating on a differential (Granada) medium compared with Lim broth enrichment (Gil et al , 1999; Votava et al , 2001), whereas other reports (De la Rosa et al , 1992; Rosa-Fraile et al , 1999) suggested that direct plating on chromogenic and or selective media was significantly less sensitive (Overman et al , 2002; Nomura et al , 2006). Comparing direct plating on SBS or CNA (bioMérieux) to that of plating on the same media after Lim broth enrichment was found to be equally sensitive with no significant advantage for enrichment (Tazi et al , 2009; El Aila et al , 2010; Louie et al , 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Limitations of Granada medium are the requirement for anaerobiasis and its limited ability at suppressing the swarming growth of Proteus sp., which was recovered from four samples. The requirement for anaerobic incubation can be circumvented by the application of a cover slide on the inoculum, as described by Rosa‐Fraile et al. (1999).…”
Section: Discussionmentioning
confidence: 99%
“…Fallon (1974) proposed the use of pigment detection as a diagnostic tool for GBS identification. This orange, brick or red pigment is unique and highly specific for GBS isolates and is used in the clinical laboratory for the identification of GBS (Fallon, 1974;Noble et al, 1983;Rosa-Fraile et al, 1999b;Spellerberg & Brandt, 2011). Nevertheless, pigment production can be variable among bovine strains and other animal species isolates (Mhalu, 1976;Merritt & Jacobs, 1978;Brglez, 1983;L€ ammler et al, 1985;Garcia et al, 2008).…”
Section: Biological Characteristicsmentioning
confidence: 99%